PERCEPÇÕES DOCENTES SOBRE O USO DE GAMES E GAMIFICAÇÃO NO ENSINO SUPERIOR: DESAFIOS E POSSIBILIDADES - SZABÓ JÚNIOR, ADALBERTO MOHAI (2020)
This research aims to analyze the insertion of gamification in the curriculum of higher education, considering its challenges and possibilities. What justifies this study from the academic point of view is the fact that, although the number of publications dealing with the object of study in this work has grown exponentially in recent years, what was evidenced during the mapping carried out in different sources, having as reference the period between 2015 and 2020, there are still teachers who may not be using such concepts in their classes because they do not know how they can be incorporated. This research seeks to answer the following problematic question: how can games and gamification encourage the engagement of higher education students? This study considers the impression that games and gamification can be used to promote student engagement, placing them as active agents. We opted for the field research methodology, of qualitative nature, of the exploratory type, based on bibliographic data, photographic records, interviews, and questionnaires. For the review of previous studies, we considered the period from 2015 to 2018 of dissertations and theses of the Bank of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES), of the Bank of Theses and Dissertations of the Methodist University of São Paulo ( UMESP) and the Brazilian Digital Library of Theses and Dissertations (BDTD). The theoretical framework that supports this work is, among others, the concept of game (HUIZINGA, 2000; MCGONIGAL, 2012 and CAILLOIS, 2017) and gamification (BURKE, 2015; ALVES, 2015 and BOLLER and KAPP, 2018). The research context involves teachers and students from a private higher education institution and, among the results found, the identification of gamification practices stands out, respecting the specificities of each circumstance, as well as their challenges and possibilities.